2023
DOI: 10.1128/mbio.00227-23
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Tolerance and Resistance Emerge at Distinct Drug Concentrations and Rely upon Different Aneuploid Chromosomes

Abstract: Antifungal drug tolerance differs from drug resistance: tolerant cells grow slowly in drug, while resistant cells usually grow well, due to mutations in a few known genes. More than half of Candida albicans clinical isolates have higher tolerance at body temperature than they do at the lower temperatures used for most lab experiments.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…These findings provide additional evidence that a distinct mechanism of FLU resistance distinguishes cluster 1 from clusters 2 and 3. The implication that different resistance mechanisms will dominate evolution in slightly different concentrations of the same drug highlights the complexity of adaptation and the need to more deeply understand the diversity of potential adaptive mechanisms before designing treatment strategies (Berman and Krysan 2020; Yang et al 2023).…”
Section: Resultsmentioning
confidence: 99%
“…These findings provide additional evidence that a distinct mechanism of FLU resistance distinguishes cluster 1 from clusters 2 and 3. The implication that different resistance mechanisms will dominate evolution in slightly different concentrations of the same drug highlights the complexity of adaptation and the need to more deeply understand the diversity of potential adaptive mechanisms before designing treatment strategies (Berman and Krysan 2020; Yang et al 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Aneuploidy is associated with the rapid evolution of azole tolerance [74,75] (Zhou et al 2024, under review). We recently found that the Chr3 and Chr6 concurrent aneuploidies conferred multi-azole tolerance via elevated drug efflux pumps (Zhou et al 2024, under review).…”
Section: Discussionmentioning
confidence: 99%
“…CNV is another important class of mutations frequently found in C. albicans strains that evolve under stress. Both whole-chromosome and segmental aneuploidy are associated with increased resistance and/or tolerance to antifungal drugs in clinical isolates and in laboratory evolution experiments [46][47][48]. In some cases, the mechanisms causing increased resistance via CNV have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…For example, amplification of the left arm of chromosome (Chr) 5 occurs via an isochromosome structure (i(5L)) that provides two additional copies of the fluconazole (FLC) target ERG11 and of a transcriptional activator of drug efflux pumps, TAC1 ; the extra copies of these two genes largely explains the drug resistance in strains carrying the i(5L) karyotype [12,49]. While the specific mechanisms of resistance have not been elucidated for most CNVs, the recurrent association of increased resistance or tolerance with specific CNVs suggests that specific genes within these amplified regions are responsible for increased resistance [46,47,50,51]. As with LOH, identifying the mechanisms of drug resistance is complicated by the large number (often hundreds) of genes amplified within a given CNV, any of which could potentially contribute to resistance via different mechanisms.…”
Section: Introductionmentioning
confidence: 99%